Agriculture in Guyana & CARICOM : essays on selected strategies for tomorrow - Smith, Winston C. (Franklin & Franklin New YorkUS, 2004)
Recognizes the important but declining role of sugar. Recommends diversification as the appropriate strategy for restoring and sustaining growth and development within the agriculture sector of Guyana and CARICOM.